The Analysis Of Mentoring, Entrepreneurship Training and Social Media on The Performance of Micro, Small, and Medium Enterprises (MSMEs) in Depok City : (Analisis Pengaruh Mentoring, Pelatihan Kewirausahaan, dan Media Sosial terhadap Kinerja Usaha Mikro, Kecil, dan Menengah (UMKM) di Kota Depok) - Elsa Tasliah; Euis Komalawati (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Micro, Small, and Medium Enterprises (MSMEs) have a strategic role in the Indonesian economy, both as contributors to Gross Domestic Product (GDP), job providers, and drivers of investment and exports. However, MSMEs face various obstacles and challenges, one of which is the economic crisis due to the Covid-19 pandemic which has a significant impact on business continuity, especially through a decrease in people's purchasing power which leads to a decrease in turnover. The Depok City Government prioritizes five main pillars in supporting the development of MSMEs, namely Training, Mentoring, Licensing Facilitation, Marketing and Access to Financing. This study aims to analyze the influence of mentoring, entrepreneurship training, and social media on the performance of micro businesses in Depok City, both partially and simultaneously. The research method used is quantitative with an explanatory approach. The research population was 1,800 micro business actors, with a sample of 100 respondents selected through purposive sampling techniques. The results of the study show that: There is a positive and significant influence of partial assistance variables on the performance of micro businesses in Depok City, with a magnitude of 22.9%. There is a positive and significant influence of the variable of entrepreneurship training partially on the performance of micro businesses in Depok City, with a magnitude of 39.8%. There is a positive and significant influence of social media variables partially on the performance of micro businesses in Depok City, with a magnitude of 16.3%. There was a positive and significant influence of the variables of mentoring, entrepreneurship training and social media simultaneously on the performance of micro businesses in Depok City by 73.8%. Abstrak Dalam perekonomian Indonesia, UMKM berperan penting sebagai kontributor terhadap Produk Domestik Bruto (PDB), penyedia lapangan kerja, dan penggerak investasi serta ekspor. Namun, UMKM menghadapi berbagai hambatan dan tantangan, salah satunya adalah krisis ekonomi akibat pandemi Covid-19 yang berdampak signifikan terhadap keberlangsungan usaha, terutama melalui penurunan daya beli masyarakat yang menyebabkan penurunan omset. Pemerintah Kota Depok memprioritaskan lima pilar utama dalam mendukung pengembangan UMKM, yaitu Pelatihan, Pendampingan, Fasilitasi Perizinan, Pemasaran, dan Akses Pembiayaan. Penelitian ini bertujuan untuk menganalisis pengaruh pendampingan, pelatihan kewirausahaan, dan media sosial terhadap kinerja usaha mikro di Kota Depok, baik secara parsial maupun simultan. Metode penelitian yang digunakan adalah kuantitatif dengan pendekatan eksploratif. Populasi penelitian adalah 1.800 pelaku usaha mikro, dengan sampel 100 responden yang dipilih melalui teknik purposive sampling. Hasil penelitian menunjukkan bahwa: Terdapat pengaruh positif dan signifikan dari variabel bantuan parsial terhadap kinerja usaha mikro di Kota Depok, dengan besaran 22,9%. Terdapat pengaruh positif dan signifikan dari variabel pelatihan kewirausahaan secara parsial terhadap kinerja usaha mikro di Kota Depok, dengan besaran 39,8%. Terdapat pengaruh positif dan signifikan dari variabel media sosial secara parsial terhadap kinerja usaha mikro di Kota Depok, dengan besaran 16,3%. Terdapat pengaruh positif dan signifikan dari variabel mentoring, pelatihan kewirausahaan, dan media sosial secara simultan terhadap kinerja usaha mikro di Kota Depok sebesar 73,8%.